Comparison of Nanotube–Protein Corona Composition in Cell Culture Media - Shannahan, Jonathan H. (2013)
In biological environments, nanomaterials associate with proteins forming a protein corona (PC). The PC may alter the nanomaterial’s pharmacokinetics and pharmacodynamics, thereby influencing toxicity. Using a label-free mass spectrometry-based proteomics approach, the composition of the PC is examined for a set of nanotubes (NTs) including unmodified and carboxylated single- (SWCNT) and multi-walled carbon nanotubes (MWCNT), polyvinylpyrrolidone (PVP)-coated MWCNT (MWCNT-PVP), and nanoclay. NTs are incubated for 1 h in simulated cell culture conditions, then washed, resuspended in PBS, and assessed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) for their associated PC. To determine those attributes that influence PC formation, the NTs are extensively characterized. NTs had negative zeta potentials in water (SWCNT-COOH < MWCNT-COOH < unmodified NTs) while carboxylation increases their hydrodynamic sizes. All NTs are also found to associate a common subset of proteins including albumin, titin, and apolipoproteins. SWCNT-COOH and MWCNT-COOH are found to bind the greatest number of proteins (181 and 133 respectively) compared to unmodified NTs (< 100), suggesting covalent binding to protein amines. Modified NTs bind a number of unique proteins compared to unmodified NTs, implying hydrogen bonding and electrostatic interactions are involved in PC formation. PVP-coating of MWCNT did not influence PC composition, further reinforcing the possibility of hydrogen bonding and electrostatic interactions. No relationships are found between PC composition and corresponding isoelectric point, hydropathy, or aliphatic index, implying minimal roles of hydrophobic interaction and pi-stacking.